Europejskie tożsamości, migracja i integracja. Młodzi europejscy migranci w dwóch zachodnich metropoliach - Bozzolo, Sandro; Costamagna, Christian; Fontana, Luisa (Człowiek i Społeczeństwo, 2014)
This paper focuses on the perception of young migrants who relocated to two Western metropolises, London and Vienna. In its majority, the target group consists of young graduates, speaking one or more foreign languages, and generally animated by a cosmopolitan spirit. The studied group consists of 11 persons interviewed in London and Vienna. Moreover, the paper is based on interviews conducted with a group of 13 leaders of a European project about migrants (Re-Turn Project). The studied groups consists of both genders in their 20s. With the analytical instruments of psychology, sociology and politology, their behaviour toward integration will be explained, as well as the matters of identity, the appropriation of cultural space and the imagined European community, still under construction. After a period of experience as migrants in a multicultural context, most of them have begun to revalue their own ethnic identity and their desire to belong to a group in which they can share a language, culture and traditions.